BACTERIAL AND FUNGAL INFECTIONS IN PULMONARY TUBERCULOSIS PATIENTS AND THE DRUG SENSITIVITY TEST PATTERNS - SINULINGGA, Cita Pujiaty; SINAGA , Bintang Yinke Magdalena; SIAGIAN, Parluhutan; YUNITA, Rina; WAHYUNI , Arlinda Sari (African Journal of Infectious Diseases (AJID), 2024)
Background: Other microbial infections in pulmonary tuberculosis (TB) patients pose significant challenges, complicating treatment outcomes and potentially increasing mortality rates. This study aims to characterize the bacterial and fungal infections profiles in pulmonary TB patients. Materials and Methods: A retrospective cross-sectional analysis was conducted at Adam Malik Hospital in Medan, Indonesia, from June 2020 to May 2022, involving inpatients diagnosed with drug-sensitive or drug-resistant TB. The data was analyzed from total sampling subjects based on medical records. Results: From 125 pulmonary TB patients, 64% had drug-sensitive TB (DS-TB) and 36% had drug-resistant TB (DR-TB), with a majority being male and underweight. Microbial analysis showed 33.6% (n=42) of the subjects exhibited bacterial growth, 8.8% (n=11) had fungal growth and 30.4% (n=38) had mixed infection. Of 80 DS-TB patients, 80% had bacterial and fungal infections compares to 60% of 45 DR-TB patients, with Microbial growth patterns was significantly difference between DS-TB and DR-TB patients, with 38.8% (n=31) of DS-TB patients displaying mixed bacterial and fungal growth, in contrast to only 15.6% (n=7) of DR-TB patients. There were no significant differences in antibiotic resistance; however, antifungal sensitivity testing revealed a significant difference in response between DS-TB and DR-TB patients, particularly to Flucytosine, Fluconazole, and Micafungin. Conclusions: There is a considerable presence of bacterial and fungal infections, with Klebsiella pneumoniae and Candida albicans being the most prevalent. The antifungal sensitivity testing suggesting a need for personalized antifungal treatment strategies between DS-TB and DR-TB patients.